Intravenous administration of lidocaine and magnesium for severe pain caused by primary chronic osteomyelitis of the mandible: A case report - Akihiko Nakamura; Daichi Hasebe; Yusuke Kato; Hideyoshi Nishiyama; Takafumi Hayashi; Tadaharu Kobayashi (Oral and Maxillofacial Surgery Cases, 2022)
Primary chronic osteomyelitis (PCO) of the jaw is a rare condition of unknown etiology with severe pain and/or facial swelling. In this article, a 63-year-old man whose severe pain caused by PCO of the mandible was treated with intravenous administration of lidocaine and magnesium is described. At the first visit, paresthesia on the right lower lip and chin was noted in an extraoral examination, and the results of an intraoral examination and laboratory examination were normal. Radiographic findings showed a ground glass-like opaque image and a bone resorption image on the right mandible. The patient was clinically diagnosed as having PCO. Pain control was difficult with conventional treatment, but successful pain control was achieved with intravenous administration of lidocaine and magnesium. The results suggested that intravenous administration of lidocaine and magnesium could be a new therapy for refractory PCO of the jaw.